Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Here is my work, with the right answer. I feel like every step is right, but somehow I am getting the wrong answer. How?

$$ \int \frac{1}{1+e^z}dz = \int\frac{1}{e^z(\frac{1}{e^z} + 1)}dz =\int\frac{1}{\frac{1}{e^z} + 1}\frac{1}{e^z}dz $$ subbing $u = \frac{1}{e^z} + 1$, $\frac{du}{dz} = -e^{-z}dz \implies -du = \frac{1}{e^z}dz$ so

$$\int \frac{1}{1+e^z}dz = -\int\frac{1}{u}du = -\ln(u) + C = -\ln(e^{-z}+1) + C$$

But the right answer is $z - \ln(1+e^z)+C$

share|cite|improve this question

Your answer is correct. $$ -\ln \left( e^{-z}+1\right) + C = -\ln \left[ e^{-z} \left( 1 + e^z\right)\right] + C = \dots $$

share|cite|improve this answer

The "right answer" is merely the simplification of the answer you found.

$$ z+\text{ln}\left(1+e^{-z}\right)==\text{ln}\left(1+e^z\right)\\ e^{z+\text{ln}\left(1+e^{-z}\right)}==e^{\text{ln}\left(1+e^z\right)}\\ e^z\left(1+e^{-z}\right)==1+e^z\\ e^z+1==1+e^z $$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.